Revision of the American Pill Millipedes I: Onomeris and Trichomeris (Diplopoda, Glomerida, Glomeridae) - Wesener, Thomas (Zootaxa, 2010)
The unique characters which distinguish Trichomeris Loomis, 1943 from Onomeris Cook, 1896 are based on erroneous drawings and not actual differences. Trichomeris is a junior synonym of Onomeris. All three species of Onomeris, O. sinuata (Loomis), 1943, O. underwoodi Cook, 1896 and O. australora Hoffman, 1950 are redescribed, based on their holotypes, as well as additional specimens. Scanning electron micrographs are presented for the first time for an American member of the order Glomerida. A key to the three species of Onomeris is provided. The available distribution data for Onomeris is still rudimentary, but the distribution areas of the three species are Cumberland Plateau from NW Alabama to Virginia for O. sinuata n. comb., lowland areas from Mississippi to Georgia for O. underwoodi, mountainous areas of Tennessee, Georgia and North Carolina for O. australora. Additional Onomeris species can potentially be discovered in the eastern United States.